Na(+)/H(+) Antiporter from Synechocystis Species PCC 6803, Homologous to SOS1, Contains an Aspartic Residue and Long C-Terminal Tail Important for the Carrier Activity - Hamada, Akira (American Society of Plant Physiologists, 2001)
A putative Na(+)/H(+) antiporter gene whose deduced amino acid sequence was highly homologous to the NhaP antiporter from Pseudomonas aeruginosa and SOS1 antiporter from Arabidopsis was isolated from Synechocystis sp. PCC 6803. The Synechocystis NhaP antiporter (SynNhaP) was expressed in Escherichia coli mutant cells, which were deficient in Na(+)/H(+) antiporters. It was found that the SynNhaP complemented the salt-sensitive phenotype of the E. coli mutant. Membrane vesicles prepared from the E. coli mutant transformed with the SynNhaP exhibited the Na(+)/H(+) and Li(+)/H(+) antiporter activities, and their activities were insensitive to amiloride. Moreover, its activity was very high between pH 5 and 9. The replacement of aspartate-138 in SynNhaP with glutamate or tyrosine inactivated the SynNhaP antiporter activity. The deletion of a part of the long C-terminal hydrophilic tail significantly inhibited the antiporter activity. A topological model suggests that aspartate-138 in SynNhaP is conserved in NhaP, SOS1, and AtNHX1 and is involved in the exchange activity. Thus, it appeared that the SynNhaP would provide a model system for the study of structural and functional properties of eucaryotic Na(+)/H(+) antiporters.